Genetic variations in angiopoietin and pericyte pathways and clinical outcome in patients with resected colorectal liver metastases. Issue 11 (17th February 2015) - Stremitzer, Stefan; Zhang, Wu; Yang, Dongyun; Ning, Yan; Stintzing, Sebastian; Sebio, Ana; Sunakawa, Yu; Yamauchi, Shinichi; Matsusaka, Satoshi; El‐Khoueiry, Rita; Stift, Judith; Wrba, Friedrich; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Genes involved in the angiopoietin and pericyte pathways may become escape mechanisms under antivascular endothelial growth factor (anti‐VEGF) therapy. The authors investigated whether variations within genes in these pathways are associated with clinical outcome in patients with colorectal liver metastases who undergo liver resection and receive perioperative, bevacizumab‐based chemotherapy. METHODS Single nucleotide polymorphisms (SNPs) in 9 genes (angiopoietin‐1 [ANGPT1]; ANGPT2; TEK tyrosine kinase, endothelial [TEK]; platelet‐derived growth factor β [PDGFB]; β‐type platelet‐derived growth factor receptor [PDGFRB]; insulin‐like growth factor 1 [IGF1]; transforming growth factor β1 [TGFB1]; RalA binding protein 1 [RALBP1]; and regulator of G‐protein signaling 5 [RGS5]) were analyzed in samples of genomic DNA from 149 patients and were evaluated for associations with clinical outcome. RESULTS RALBP1 reference SNP 329007 (rs329007) A>G resulted in a significant difference in recurrence‐free survival (A/A genotype, 14.0 months; A/G or G/G genotype, 9.2 months; hazard ratio [HR], 1.60; P = .024). PDGFB rs1800818 A>G was associated with 3‐year overall survival rates (A/A genotype, 78%; A/G genotype, 69%; [HR 1.37]; G/G genotype, 53%; [HR 2.12]; P = .048). In multivariate analysis, RALBP1 rs329007 A>G remained significant (HR, 1.99; P = .002). PDGFB rs1800818 A>G and RALBP1 rs329007 A>G were correlated with radiologic response (A/A or A/G genotype, 86%; G/G genotype, 71% [P = .042]; A/A genotype, 78%; A/G or G/G genotype, 94% [P = .018], respectively). RALBP1 rs329007 A>G demonstrated significantly different rates of histologic response (A/A genotype: major histologic response, 35%; partial histologic response, 34%; no histologic response, 30%; A/G or G/G genotype: 46%, 13%, and 41%, respectively; P = .029). Recursive partitioning analysis revealed that ANGPT2 rs2442599 T>C and RALBP1 rs329007 A>G were the main SNPs that predicted histologic response and recurrence‐free survival, whereas PDGFB rs1800818 A>G was the leading SNP that predicted overall survival. ANGPT2 rs2916702 C>T and rs2442631 G>A were significantly associated with the probability of achieving a cure. CONCLUSIONS The current data suggest that variations in genes involved in the angiopoietin and pericyte pathways may be predictive and/or prognostic biomarkers in patients with resected colorectal liver metastases who receive bevacizumab‐based chemotherapy. Cancer 2015;121:1898–1905. © 2015 American Cancer Society.